2017
DOI: 10.1108/jfm-11-2016-0047
|View full text |Cite
|
Sign up to set email alerts
|

User requirement related performance attributes for government residential buildings

Abstract: Purpose Present research on assessing performance of residential buildings is done for specific purposes and not holistically. The indicators, factors and attributes considered for evaluation are not consistent and are broadly based on knowledge base of the author. The purpose of this research is to identify building performance attributes based on user requirement. Design/methodology/approach With ISO 6241-1984(E) as a basis for universal acceptance, user requirements have been listed and based on these use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…A list of facilities performance attributes was generated from these publications. The attributes considered are those that have a direct influence on user satisfaction (Seshadhri and Paul, 2017). Due to the diversity of performance attributes in the literature, the insights from academia, facility managers and users of higher education buildings were sought to extract relevant attributes.…”
Section: Research Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…A list of facilities performance attributes was generated from these publications. The attributes considered are those that have a direct influence on user satisfaction (Seshadhri and Paul, 2017). Due to the diversity of performance attributes in the literature, the insights from academia, facility managers and users of higher education buildings were sought to extract relevant attributes.…”
Section: Research Approachmentioning
confidence: 99%
“…In this case, the satisfaction with an education space reflects the degree to which the users perceive how the space's facilities performance attributes facilitate their academic activities and well-being. Satisfaction can also be the absence of user complaints (Seshadhri and Paul, 2017), making satisfaction the complimentary approval of contentment from end-users. In its application, user satisfaction is mostly measured with an occupant survey (Cleveland and Fisher, 2014;Li et al, 2018).…”
Section: User Satisfaction and Facilities Performance Attributesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also obvious that the provision of ample carparks directly affects the success of business activities, especially in shopping malls (Sepe and Pitt, 2017). The availability of adequate parking facilities should also feature as an important performance attribute of residential buildings (Seshadhri and Kumar, 2017). Earlier on, many planning initiatives have been undertaken to provide additional car park spaces, such as the integration of multi-storey car parks in public housing estates in Singapore, even at the expenses of possible air quality impairment, privacy intrusion and noise to nearby residents (Wong and Ling, 2003).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Based on the extensive literature review highlighted in preceding sections of this paper, finally seven factors were identified as BPAs essential to be measured to assess building performance (Gopikrishnan and Paul, 2016) (Seshadhri and Paul, 2016). Seven BPAs are grouped into built form and environmental factors directly related to building performance.…”
Section: Building Performance Attributesmentioning
confidence: 99%